ISOLATION AND IDENTIFICATION OF MYCOFLORA FROM MAIZE SEEDS AND THEIR IMPACTS ON PROTEIN QUALITY - Rani, Lucky; Prasad, Gajendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Maize is one of the major food crops around the world and it provides energy for human and animals. It grows throughout the year due to its photothermo insensitive character and highest genetic yield. The composition of maize contents are Moisture 14.9% , Fat 3.6% , Fibre 2.7 % , Minerals 1.5 % and Protein 11.5% respectively. The economic value of the protein contents are utilized in the production of food products .The various genera of fungi like .Aspergillus, Penicillium , Alternaria, Fusarium and Rhizopus were recorded from maize sample of Var. A and Var. B . The dominant fungi A. flavus (760 which produce toxic substance like Aflatoxin B1 . Aflatoxin B1 known to adverse the seed germination and decline the quality ( Protein ) contents . The inhibition of seed germination were maximum 74.67% and 75.67% in both the Var. A and Var B. at 2000 ppb concentration of aflatoxin B1 respectivily , whereas the maximum inhibition of protein contents ( 73.34% and 49.36 % ) in Var. A and Var. B were also recored at 2000ppb concentration of aflatoxin B1 ,respectively Therefore , The healthy maize seeds should be released to the farmers in order to the secure their outputs as well as to provide the quality of energetic food for the human beings.